2019
DOI: 10.1039/c9tc01209e
|View full text |Cite
|
Sign up to set email alerts
|

Adverse oxidation of CsPbI2Br perovskite during the crystallization process in an N2 glove-box

Abstract: During annealing, surface oxidation leads to defect formation in the crystals and attenuated photovoltaic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In a very recent report, it has been found that CsPbI 2 Br undergoes adverse oxidation during the annealing process even in N 2 ‐filled glove box and the Pb‐O sites generated during the process function as defects being detrimental for device performance. More of such thorough investigations, which are expected to come in future, can contribute significantly to the understanding of defect formation and passivation . Phase purity, chemical composition uniformity and microdefects must be examined well to find the actual role of dopants and additives in passivating the defects.…”
Section: Inorganic (Organic‐free) Perovskitesmentioning
confidence: 99%
“…In a very recent report, it has been found that CsPbI 2 Br undergoes adverse oxidation during the annealing process even in N 2 ‐filled glove box and the Pb‐O sites generated during the process function as defects being detrimental for device performance. More of such thorough investigations, which are expected to come in future, can contribute significantly to the understanding of defect formation and passivation . Phase purity, chemical composition uniformity and microdefects must be examined well to find the actual role of dopants and additives in passivating the defects.…”
Section: Inorganic (Organic‐free) Perovskitesmentioning
confidence: 99%
“… Subsequently, the CsPbBr 3 with the accumulation of holes further produces oxidative products. Besides, as for the oxygen degradation mechanism of CsPbI 2 Br, it has been concluded that oxygen atoms are chemically absorbed at the surface and thus interstitial oxygen defects generate The oxygen degradation also appears in HTL due to the oxidation of organic HTM.…”
Section: Degradation In Moisture and Oxygen Environmentmentioning
confidence: 99%
“…were also very promising HTL candidates due to their excellent thermal stability, but their fabrication condition need be to be further optimized. [16,[137][138][139][140]…”
Section: Charge Transfer Layermentioning
confidence: 99%